PENGARUH LIKUIDITAS, SOLVABILITAS DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2019 - Marintan Saragih (UNHI Press, 2021)
This study aims to see the effect of liquidity, solvency, and profitability on share prices in mining companies listed on the Indonesia Stock Exchange in 2017-2019. Several previous studies regarding different stock prices. The study population was 46 mining companies. The sampling method used was purposive sampling method, in order to obtain 20 sample companies for 3 years of observation (2017 - 2019) with 60 observations. In data management, there are 4 data that must be discarded so that the data is normal so that the observation data in the study is 56 data. The research data were obtained from sample companies which can be downloaded from the Indonesia Stock Exchange website. The data analysis technique used is descriptive statistical analysis and multiple regression analysis. The data analysis process that is done first is descriptive statistics, classical assumption test, multiple analysis and then testing the hypothesis. Simultaneously, liquidity, solvency and profitability have a significant effect on stock prices. Partially liquidity has a positive but not significant effect on stock prices. Solvency has no effect on stock prices. And profitability has a significant positive effect on stock prices